Effect of bank financing on exports and imports of reciprocal commodities in Sudan - Mohammed, Emad Sulaiman Sharif; Saleh, Sondos Atef Jalal (Journal of Economic, Administrative and Legal Sciences, 2017)
This empirical study aims to highlight the relationship between exports and imports on the one hand and the financing of foreign trade in Sudan. If we ignore the meteorologic and the political factors and international economic variability, It is supposed that This relationship is positive so the increase of the bank financing size leads to an increase in the volume of foreign trade.And to prove it, we have adopted and analytical and deductive approach applied to a sample of economic and banking data from 2004 to 2012.The results showed that there is a continuous increase in the volume of exports in line with the increase in financing granted for exports. However, there is a fluctuation in the imports financing which was accompanied by a fluctuation in the volume of imports. The study recommended more attention to the export subsidies in addition to the continuous and systematic support to the imports.